ANALISIS EFEKTIFITAS DAN PERTUMBUHAN PENDAPATAN ASLI DAERAH PADA DINAS PENDAPATAN DAERAH KOTA MAKASSAR - Idrawahyuni Idrawahyuni (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine the effectiveness and growth of local revenue at the Makassar City Regional Revenue Service. This type of research is descriptive quantitative. The population of this study is the financial statements of the Makassar City Regional Revenue Service. Samples were taken from the financial statements of the Makassar City Regional Revenue Service office in the last five years, from 2013 to 2017. The results of data analysis used the ratio of effectiveness and growth of local revenue, which showed that the two financial ratio analyzes were classified as effective.